An Analysis of The Word Formation in Captain Marvel Movie - Rantung, Christina; Kamagi, Sarah; Rettob, Alloysius (Journal of English Culture, Language, Literature and Education, 2024)
This study analyzes the word formation processes in the Captain Marvel movie, aiming to identify the types and mechanisms of word formation present in the film. Employing a qualitative research method, data were gathered through repeated viewings of the movie and careful examination of its script. The analysis followed the framework proposed by Miles and Huberman (1994), involving data reduction, data display, and conclusion drawing. The findings revealed 64 instances of word formation, categorized into six distinct types. These included nine examples of borrowing, 38 instances of compounding, five instances of clipping, two instances of conversion, three instances of acronyms, and five instances of derivation. Among these, compounding emerged as the most frequently used word formation process, with 38 examples identified. This research highlights the diverse linguistic features embedded in the language of Captain Marvel, with a notable emphasis on compounding as a dominant process. The study provides insights into the dynamic use of word formation in cinematic scripts and contributes to a broader understanding of language in media.